The problem of simulation of nonzsinusoidal modes in distributed networks - Nikolay Nikolaevich Kharlov; Vasily Yakovlevich Ushakov; Evgeny Vladimirovich Tarasov; Leonid Leonidovich Bulyga (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the research of non-sinusoidal modes in distributed network consists in gathering full information about the efficiency of electric energy transportation. Prediction of voltage quality indices and electrical energy losses in network units should provide losses level minimization and tends to improve quality. The main aim of the research is to study the correlations and statistical distributions of higher harmonics of nodal voltages/currents in distributed networks 110 kV, to determine smoothing functions forcalculating Stochastic mode of networks. The methods of the research. The authors have used the software implemented in Fortran programming to simulate the non-sinusoidal modes of distributed networks. The data for calculation were obtained during energy survey of Interregional Distribution Grid Company of Siberia, namely such branches as: «Altaienergo», «Buriatenergo» and «Krasenergo». The required data were collected by using portable power analyzer AR-5 «Circutor». Voltage and current oscillograms, consisting of 128 point, were expanded in the Fourier series. The authors analyzed the correlation dependences of fundamental harmonic and higher harmonics of voltage and current. Smoothing of statistical distributions and obtaining their analytical dependencies were achieved using probability distribution in a series based on the Gauss distribution. The results. The authors determined the statistical properties of higher harmonics distributions in nodal voltages/currents and studied the statistical distributions of higher harmonics modules in nodal voltages/currents, which allowed determining uni- and multimodal dependencies of statistical distribution and smoothing quality.